Ethics: Wittgenstein’s Radical Ethics - Hannes Nykänen (EJP import test, 2019)
Summary: In this paper I will show how the later Wittgenstein utilises the “logic” of the second-person or I-you perspective. Though Wittgenstein himself did not think of his philosophy in this way, laying out the logic of the I-you understanding will show the source of the illuminating power of his philosophy and give a perspicuous view of the character of philosophical problems. Philosophers tend to overlook that a fundamental form of intelligibility has its source in the second person or I-you perspective. The most salient feature of the I-you perspective is its ethical character and I will try to outline some aspects of this feature. When ethics is understood in terms of the I-you perspective it will differ radically from the way ethics is understood in the philosophical mainstream. This may explain why it has been so difficult for Wittgenstein-scholars to give a clear account of the way ethics is essential to Wittgenstein’s later philosophy. I will try to show the philosophical significance of the I-you perspective by discussing both some of Wittgenstein’s problematic ideas such as his talk of first person expressive and third person descriptive perspectives and some of his fruitful ideas such as his talk of primitive reactions and language-games, in the light of the I-you perspective.
Keywords: conscience; Ethics; I-you understanding; repression; Wittgenstein